PENERAPAN PBL BERBANTUAN INTERACTY CROSSWORD PUZZLE UNTUK MENINGKATKAN HASIL BELAJAR - Hamzah, Nurain Afiat Ramandhian; Panai, Abdul Haris; Arif, Rifda Mardian; Arifin, Irvin Novita; Kudus, Kudus (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2025)
The low learning outcomes of fourth-grade students in the subject of Science (IPAS) at SDN 9 Limboto prompted the need for innovation in teaching practices. Preliminary studies revealed that most students did not meet the minimum mastery criteria (KKM), and the learning process remained conventional without digital media support. This study aims to improve student learning outcomes through the implementation of the Problem Based Learning (PBL) model assisted by web-based crossword puzzle media using Interacty. The research employed a Classroom Action Research (CAR) approach, conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected using observation sheets for teacher and student activities, learning outcome tests, documentation, and interviews. The findings show a significant improvement in student mastery, from 38.89% in the first cycle to 83.33% in the second cycle. Teacher and student engagement also increased markedly with the optimal use of interactive learning media. It is concluded that the PBL model assisted by Interacty-based crossword puzzle media is effective in enhancing student learning outcomes on the topic of energy. This model and media are recommended for use in elementary science learning to create engaging, active, and meaningful educational experiences. ABSTRAKRendahnya hasil belajar siswa pada mata pelajaran IPAS di kelas IV SDN 9 Limboto menjadi latar belakang perlunya inovasi dalam pembelajaran. Studi pendahuluan menunjukkan bahwa sebagian besar siswa belum mencapai kriteria ketuntasan minimal (KKM), dan pembelajaran masih bersifat konvensional tanpa dukungan media digital. Penelitian ini bertujuan untuk meningkatkan hasil belajar siswa melalui penerapan model Problem Based Learning (PBL) berbantuan media crossword puzzle berbasis web Interacty. Penelitian ini menggunakan pendekatan Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus, masing-masing terdiri dari tahapan perencanaan, tindakan, observasi, dan refleksi. Instrumen penelitian mencakup observasi aktivitas guru dan siswa, tes hasil belajar, dokumentasi, serta wawancara. Hasil penelitian menunjukkan bahwa terjadi peningkatan ketuntasan belajar siswa dari 38,89% pada siklus I menjadi 83,33% pada siklus II. Aktivitas guru dan siswa juga meningkat secara signifikan seiring dengan optimalisasi penggunaan media pembelajaran interaktif. Simpulan dari penelitian ini adalah bahwa penerapan model PBL berbantuan media crossword puzzle berbasis Interacty terbukti efektif dalam meningkatkan hasil belajar siswa pada materi energi. Model dan media ini direkomendasikan untuk diterapkan dalam pembelajaran IPAS di sekolah dasar guna menciptakan pembelajaran yang aktif, menarik, dan bermakna.